2020
DOI: 10.2478/pjst-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of External Attentional Focus and Self-Controlled Feedback on Motor Learning in Older Adults

Abstract: Introduction. External focus instruction and self-controlled feedback have beneficial effects on motor learning. The purpose of the present study was to investigate the benefits of combined effects of external focus instruction and self-controlled feedback on balance performance in older adults.Material and Methods. Forty older adults (mean age: 63.21 ± 3.6 years; all female) were selected and randomly divided into 4 groups: self-controlled feedback, external attention, external attention/self-controlled feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Under dual-task conditions, due to simultaneously concentrating on primary and secondary tasks, individuals may automatically shift their attention to external cues. A large body of the existing studies confirms that using external focus of attention results in a greater improvement in motor, and even cognitive, learning and functions, including working memory, compared to cases where internal focus of attention is used (Razaghi et al, 2020;Wulf, 2013). In this regard, Wulf et al, (2013) put forth the constrained action hypothesis, arguing that, while using external attention, individuals improve their motor learning and performance through facilitating automatic processes in their motor systems while in cases where the external focus of attention is employed, learners often disrupt these automatic processes, undermining their motor performances.…”
Section: Discussionmentioning
confidence: 94%
“…Under dual-task conditions, due to simultaneously concentrating on primary and secondary tasks, individuals may automatically shift their attention to external cues. A large body of the existing studies confirms that using external focus of attention results in a greater improvement in motor, and even cognitive, learning and functions, including working memory, compared to cases where internal focus of attention is used (Razaghi et al, 2020;Wulf, 2013). In this regard, Wulf et al, (2013) put forth the constrained action hypothesis, arguing that, while using external attention, individuals improve their motor learning and performance through facilitating automatic processes in their motor systems while in cases where the external focus of attention is employed, learners often disrupt these automatic processes, undermining their motor performances.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, future studies are recommended to analyze the impact of internal and external (proximal and distal) attentional focus while using other strokes in table tennis. What is more, Razaghi et al [ 42 ] suggest that the combinations of external focus instructions and self-controlled feedback should be used to improve performance and motor learning outcomes. Also, Makaruk et al [ 43 ] propose that a combination of external attentional focus with autonomy support may produce benefits in motor performance.…”
Section: Discussionmentioning
confidence: 99%
“…Research has largely demonstrated that focusing outside the body and on the intended outcome of the movement (i.e., external focus) yields better results in learning and movement performance than focusing on body parts, specific movements, or mechanics (i.e., internal focus) ( Neumann, 2019 ). External attentional focus has been shown to result in increased movement efficiency (e.g., reduced muscle activity, higher peak force), movement performance (e.g., better balance, greater accuracy, greater speed, better endurance), a better movement form, as well as more automatic and fluent movements ( Artymiak et al, 2017 ; Razaghi et al, 2020 ; Wulf and Lewthwaite, 2016 ).…”
Section: Introductionmentioning
confidence: 99%